MicroRNA-124/Death-Associated Protein Kinase 1 Signaling Regulates Neuronal Apoptosis in Traumatic Brain Injury via Phosphorylating NR2B - Shi, Yingwu; Cui, Wenxing; Wang, Qiang; Zhou, Jinpeng; Wu, Xun; Wang, Jin; Zhang, Shenghao; Hu, Qing; Han, Liying; Du, Yong; Ge, Shunnan; Liu, Haixiao; et al. (Frontiers in Cellular Neuroscience, 2022)
Death-associated protein kinase 1 (DAPK1), a Ca2+/calmodulin-dependent serine/threonine-protein kinase, promotes neurons apoptosis in ischemic stroke and Alzheimer's disease (AD). We hypothesized that knockdown DAPK1 may play a protective role in traumatic brain injury (TBI) and explore underlying molecular mechanisms. ELISA, Western blotting, immunofluorescence, dual-luciferase assay, and RT-qPCR were used to determine the mechanism for the role of DAPK1 in TBI. Open field and novel objective recognition tests examined motor and memory functions. The morphology and number of synapses were observed by transmission electron microscopy and Golgi staining. DAPK1 was mainly found in neurons and significantly increased in TBI patients and TBI mice. The dual-luciferase assay showed that DAPK1 was upregulated by miR-124 loss. The number of TUNEL+ cells, expression levels of cleaved caspase3 and p-NR2B/NR2B were significantly reduced after knocking-down DAPK1 or overexpressing miR-124 in TBI mice; and motor and memory dysfunction was recovered. After Tat-NR2B were injected in TBI mice, pathological and behavioral changes were mitigated while the morphology while the number of synapses were not affected. Overall, DAPK1 is a downstream target gene of miR-124 that regulates neuronal apoptosis in TBI mice via NR2B. What’s more, DAPK1 restores motor and memory dysfunctions without affecting the number and morphology of synapses.